Kražiai Market Town in Interwar Years: Life, Organizations, Personalities - Mažonas, Vygantas (Lietuvos istorijos studijos, 2025)
By referring to historiography materials, printed mass media and photo-testimony, the article reveals a generalized view of Kražiai, a minor town, during the interwar years. Research starts with demography data of the small-town residents, and proceeds with the stories of the vital institutions and organizations of the town, by identifying them and revealing certain instances in the course of their development. This analysis ranges from Kražiai Volost and Kražiai Gymnasium to Non-Religious Ethical Culture Society Kražiai Department. The article also introduces the key personalities and most respected individuals of Kražiai Town at the time. This ensures better understanding of whoever was the elite of Kražiai Town and other smaller towns in general at the time, while also highlighting the structure of society at that time.